Augmented-reality within computer assisted orthopaedic surgery workflows: a proof of concept study - Iqbal,H; Tatti,F; Rodriguez,Y Baena F (EasyChair, 2019)
The integration of augmented-reality (AR) in medical robotics has been shown to reduce cognitive burden and improve information management in the typically cluttered environment of computer-assisted surgery. A key benefit of such systems is the ability to generate a composite view of medical-informatics and the real environment, streamlining the pathway for delivering patient-specific data. Consequently, AR was integrated within an orthopaedic setting by designing a system that captured and replicated the user- interface of a commercially available surgical robot onto a commercial head mounted see through display. Thus, a clinician could simultaneously view the operating-site and real- time informatics when carrying out an assisted patellofemoral-arthroplasty (PFA). The system was tested with 10 surgeons to examine its usability and impact on procedure- completion times when conducting simulated PFA on sawbone models. A statistically insignificant mean increase in procedure completion-time (+23.7s, p=0.240) was found, and the results of a post-operative qualitative-evaluation indicated a strongly positive consensus on the system, with a large majority of subjects agreeing the system provided value to the procedure without incurring noticeable physical discomfort. Overall, this study provides an encouraging insight into the high levels of engagement AR has with a clinical audience as well as its ability to enhance future generations of medical robotics.